BET 1: To debrief or not debrief. Issue 7 (18th July 2019) - Timms, Victoria
Abstract : A short cut review was carried out to establish whether a staff debriefing session after involvement in a traumatic resuscitation reduces stress and anxiety, reduces sickness, improves team working and morale and improves staff retention. Four papers presented the best evidence to answer the question. The author, date and country of publication, group studied, study type, relevant outcomes, results and study weaknesses of these papers are tabulated. It is concluded that there is no evidence about the efficacy of team debriefing in the ED. However, there is some desire among staff for it to occur. Further research is needed and in the meantime local advice should be followed.